Improvement of alfalfa forage quality and management through the down-regulation of MsFTa1 - Lorenzo, Christian Damián (2019)
Alfalfa (Medicago sativa L.) is one of the most important forage crops worldwide. As a perennial, alfalfa is cut several times each year. Farmers face a dilemma: If cut earlier, forage nutritive value is much higher but regrowth is affected and the longevity of the stand is severely compromised. On the other hand, if alfalfa is cut later at full flower, stands persist longer, more biomass may be harvested, but the nutritive value diminishes. Alfalfa is a strict long‐days plant. We reasoned that by manipulating the response to photoperiod, we could delay flowering to improve forage quality and widen each harvesting window, facilitating management. With this aim, we functionally characterised the FLOWERING LOCUS T family of genes, represented by five members: MsFTa1, MsFTa2, MsFTb1, MsFTb2 and MsFTc. The expression of MsFTa1 correlated with photoperiodic flowering and its downregulation led to severe delayed flowering. Altogether, with late flowering, low expression of MsFTa1 led to changes in plant architecture resulting in increased leaf to stem biomass ratios and forage digestibility. By manipulating photoperiodic flowering we were able to improve the quality of alfalfa forage and management, which may allow farmers to cut alfalfa of high nutritive value without compromising stand persistence.